2018
DOI: 10.1159/000489364
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Tyrobutyricum Protect Intestinal Barrier Function from LPS-Induced Apoptosis via P38/JNK Signaling Pathway in IPEC-J2 Cells

Abstract: Background/Aims: The intestinal mucosa forms a physical and metabolic barrier against the diffusion of pathogens, toxins, and allergens from the lumen into the circulatory system. Early weaning, a critical phase in swine production, can compromise intestinal barrier function through mucosal damage and alteration of tight junction integrity Maintenance of intestinal barrier function plays a pivotal role in optimum gastrointestinal health. In this study, we investigated the effects of Clostridium tyrobutyricum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…Previous studies found that LPS can induce cells apoptosis, which also promotes the production of inflammatory factors (Xiao et al, 2018). To examine the effect of APS on LPS‐stimulated IPEC‐J2 cells apoptosis, cells apoptosis and necrosis were assessed by Annexin‐V‐FITC/PI double staining.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies found that LPS can induce cells apoptosis, which also promotes the production of inflammatory factors (Xiao et al, 2018). To examine the effect of APS on LPS‐stimulated IPEC‐J2 cells apoptosis, cells apoptosis and necrosis were assessed by Annexin‐V‐FITC/PI double staining.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies found that LPS can induce cells apoptosis, which also promotes the production of inflammatory factors (Xiao et al, 2018).…”
Section: Aps Suppressed Lps-induced Cells Apoptosis In Ipec-j2 Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…p38 MAPK is a serine/threonine kinase that is activated by the phosphorylation of Thr180 and Tyr182 residues in response to different stress signals [25] and can promote cell apoptosis [26]. Upstream activators of p38 include Src1 [27,28] and Rac1 [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the effector of Salmonella enteritidis AvrA could stabilize TJ protein ZO-1 and attenuate bacterial invasion via inhibition of the JNK signaling pathway [41]. The downstream genes of the JNK signaling pathway, including AP-1, c-Jun, ATF-2 and ELK-1, are reported to regulate epithelial barrier functions [41][42][43][44][45]; further study is required to determine which downstream molecules in the JNK pathway were activated by PCV2.…”
Section: Discussionmentioning
confidence: 99%